Visual Problems Affecting Reading and Learning Among Primary School Children in Benin City, Nigeria. - Atuanya, George Nnamdi; Suzan, Obehi Idogen (Optometry & Visual Performance, 2024)
Background: Reading is a complex cognitive process that involves visual perception, attention, memory, and language skills. Children with visual problems may experience difficulties in several aspects of reading, such as word recognition, comprehension, fluency, and speed. This can ultimately affect their ability to read and to learn without the hindrance of visual discomfort. This study aims to determine the relationship between visual problems and reading and learning ability among primary school children in Benin-City, Nigeria. Method: A cross-sectional study was conducted, and the participants were recruited from three primary schools in Benin-City. A comprehensive visual screening was performed to assess visual acuity, refractive status, color vision, ocular motility, and ocular alignment status of the participants. A test of visual sequential memory was used to assess the visual perceptive skills of the participants as a measure of their ability to read and to learn. Results: A total of 300 primary school children (151 males and 149 females) with a mean age of 9.68 ± 1.756 years took part in this study. Out of the 155 participants who failed the test, 81 were discovered to have visual problems. This study's results showed an association between refractive error and scores on the visual sequential memory test (p=0.027). Conclusion: We concluded from this study that visual problems could negatively affect reading and learning abilities in primary school children. This study emphasizes the importance of promptly addressing visual problems in primary school children as a necessity to mitigate the risk of poor reading and learning abilities among these children. This study also highlights the importance of school screening programs for the early identification of school children with visual problems.